Chronic Consumption of Bovine Dairy Milk Attenuates Dietary Saturated Fatty Acid-Induced Blood-Brain Barrier Dysfunction - D'Alonzo, Zachary; Lam, Virginie; Nesbit, Michael; Graneri, Liam; Takechi, Ryu; Mamo, John C. L. (Frontiers in Nutrition, 2020)
Ingestion of Western-diets enriched in long chain saturated fatty acids (LCSFA) are associated with increased risk of blood-brain barrier (BBB) dysfunction and neurovascular inflammation. Potential mechanisms include vascular insult as a consequence of metabolic aberrations, or changes in capillary permeability resulting in brain parenchymal extravasation of pro-inflammatory molecules. Bovine dairy milk (BDM) is potentially a significant source of dietary LCSFA, however, BDM contains an array of bioactive molecules purported to have vascular anti-inflammatory properties. This study investigated the effects of full cream (4% total fat) and delipidated (skim) BDM on BBB integrity and neuroinflammation in wild-type mice. Mice consuming substantial amounts of full cream or skim BDM with LCSFA-enriched chow were dyslipidemic compared to control mice provided with standard chow and water. However, there was no evidence of BBB dysfunction or neuroinflammation indicated by parenchymal abundance of immunoglobulin G and microglial recruitment, respectively. Positive control mice maintained on an LCSFA-enriched diet derived from cocoa-butter and water, had marked BBB dysfunction, however, co-provision of both full cream and skim milk solutions effectively attenuated LCSFA-induced BBB dysfunction. In mice provided with low-fat chow and full cream BDM drinking solutions, there were substantial favourable changes in the concentration of plasma anti-inflammatory cytokines. This study suggests that consumption of BDM may confer potent vascular benefits through the neuroprotective properties exuded by the milk-fat globule membrane moiety of BDM.